2018
DOI: 10.1111/lcrp.12136
|View full text |Cite
|
Sign up to set email alerts
|

Collective interviewing: The use of a model statement to differentiate between pairs of truth‐tellers and pairs of liars

Abstract: Purpose. The current experiment examined the use of a model statement for aiding lie detection and gathering additional information during interviews in which pairs of suspects were interviewed together (i.e., collective interviewing). A model statement is an example of an answer, unrelated to the topic under investigation, which is played to suspects to demonstrate how much information the interviewer wants them to provide in response to the question asked.Method. Pairs of truth-tellers visited a restaurant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The current project is part of a larger project. In the other part of the project, a model statement manipulation in a collective interview setting was examined (Vernham, Vrij, & Leal, ). The 49 British pairs in this study were part of a 67 pairs of control group of the other study, which also included 18 pairs of non‐British participants (not the Chinese and Arab participants of the current sample).…”
Section: Methodsmentioning
confidence: 99%
“…The current project is part of a larger project. In the other part of the project, a model statement manipulation in a collective interview setting was examined (Vernham, Vrij, & Leal, ). The 49 British pairs in this study were part of a 67 pairs of control group of the other study, which also included 18 pairs of non‐British participants (not the Chinese and Arab participants of the current sample).…”
Section: Methodsmentioning
confidence: 99%
“…The interaction effects for the new total details in the second recall and reverse order recalls were not significant (both F's < .40, both p's > .532), which replicates Leal et al (2018). However, for the reason described above, we -and also Leal et al (2018a)-examined the Veracity effects for the two Model Statement conditions separately, see Table 3.…”
Section: About Herementioning
confidence: 58%
“…In that study, using British participants, it was found that a model statement elicited more peripheral details in liars than in truth tellers. Investigators are typically interested in whether tools that work in Western cultures also work in other cultures (Leal et al, ; Vernham, Vrij, & Leal, ). To answer this question, cross‐cultural research is required.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there have been 17 published studies using a MS and two studies reported at conferences (Hirn et al, 2012; Körner & Urban, 2018). One study used pairs of participants, and although the MS appeared useful for facilitating lie‐detection, this has only been tested once (Vernham, Vrij, & Leal, 2018). As we are interested in individual participants, this study has not been included in the review.…”
Section: Resultsmentioning
confidence: 99%